LEGAL PROTECTION AGAINST CHILDREN WHO ARE VICTIMS OF HUMAN TRAFFICKING IN CIANJUR DISTRICT STUDIED BY HUMAN RIGHTS PERSPECTIVE - Henny Nuraeny; Tanti Kirana Utami (Faculty of Law, Universitas Jenderal Soedirman, 2015)
Trafficking in persons is a modern form of slavery. The eradication of human trafficking has been on the agenda in law enforcement because of its effects can interfere with social welfare. One form of trafficking in persons who lately is rampant child trafficking. The problems that can be studied is how the perspective of Human Rights in providing protection to children who are victims of trafficking and whether the implementation of legal protection for child victims of trafficking in Cianjur is in line with the concept of human rights. This study uses normative juridical approach and specification of descriptive analysis. Results from this study is the protection of child victims of trafficking in persons has been referred to the concept of human rights which the regional government make policies on prevention of trafficking, rehabilitation, counseling and empowerment of victims of human trafficking. Keywords: human rights, legal protection, trafficking